2003
DOI: 10.1034/j.1399-6576.2003.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain relief and safety after major surgery A prospective study of epidural and intravenous analgesia in 2696 patients

Abstract: Pain relief and safety after major surgery A prospective study of epidural and intravenous analgesia in 2696 patients. Link to publication Citation for published version (APA): Flisberg, P., Rudin, Å., Linnér, R., & Lundberg, C. J. F. (2003). Pain relief and safety after major surgery A prospective study of epidural and intravenous analgesia in 2696 patients. Acta Anaesthesiologica Scandinavica, 47(4), 457-465. DOI: 10.1034457-465. DOI: 10. /j.1399457-465. DOI: 10. -6576.2003 General rights Copyright and moral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 61 publications
4
59
1
4
Order By: Relevance
“…Mann et al 19 conclude that epidural local anesthetics with opioid improve mental status compared with IV-PCA. Th e study performed by Flisberg et al 33 showed that patients with EA were less confused compared with patients with iv morphine analgesia. Th e lower incidence of postoperative delirium in TEA group could be attributed to superior pain therapy and reduced opioid consumption, earlier recovery of postoperative ileus, and initiation of oral feeding, lower levels of sedation and more effi cient mobilization 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mann et al 19 conclude that epidural local anesthetics with opioid improve mental status compared with IV-PCA. Th e study performed by Flisberg et al 33 showed that patients with EA were less confused compared with patients with iv morphine analgesia. Th e lower incidence of postoperative delirium in TEA group could be attributed to superior pain therapy and reduced opioid consumption, earlier recovery of postoperative ileus, and initiation of oral feeding, lower levels of sedation and more effi cient mobilization 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A large patient sample in the study performed by Flisberg et al 33 showed that patients with EA had better analgesia after major surgery with a reduced incidence of respiratory depression and sedation compared with patients with iv morphine analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…I T has been shown that postoperative epidural analgesia provides better dynamic pain control and reduces overall mortality compared with traditional postoperative treatment modalities (1)(2)(3). However, serious complications such as spinal hematoma with neurological deficits following epidural and spinal anesthesia may lead to a devastating situation for the individual patient.…”
mentioning
confidence: 99%
“…The drug of choice using epidural analgesia is local anesthetics but in the interest of improving efficacy of pain control, opioids are usually added. However epidural opioids may cause pruritis and urinary retention [10,12,14] and the risks associated with placing epidural catheters are low but may include epidural hematomas, infections and catheter migration into the thecal sac area [12].…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of epidural anesthesia are early ambulation and related decrease in pulmonary complications [6,7], nausea and sedation compared to systemic opiate pain control [8][9][10]. Pain control is often better achieved using epidural anesthesia than with IV narcotics [12][13][14][15]. Patients show less of a stress response determined by lower circulating levels of epinephrine, norepinephrine, cortisol and serum glucose [11].…”
Section: Introductionmentioning
confidence: 99%